SELF-DETERMINATION THEORY AND MOVEMENT TECHNOLOGY IN COLLEGE PHYSICAL ACTIVITY CLASSES - Nanney, Lindsey (East Carolina University, 2014)
The college-age population is not sufficiently physically active and physical activity declines markedly during the college years. Interventions in university and college settings are potential avenues for increasing physical activity in this population. PURPOSE: The purpose of this study was to examine the effect of need-supportive class environments and conventional class environments, with and without the use of movement technology, on college students' self-determined motivation for physical activity and physical activity levels. A secondary purpose was to examine changes in physical activity enjoyment and physical activity Stage of Change. METHODS: The thesis was designed as a main study and a substudy. For the main study, a self-determination theory based, need-supportive teaching intervention was developed and implemented with a group of randomly selected graduate student instructors (n = 7) of a basic instruction college physical activity class (n = 34 classes and 730 students). The other instructors (n = 7) received conventional training for graduate student instructors and were told to teach as usual (n = 36 classes and 775 students). Students (N = 1,505, M age = 19.4 ± 1.4 years) completed online questionnaires at the beginning, middle, and end of the semester. Self-determined motivation was assessed with the Revised Behavior Regulation in Exercise Questionnaire. Physical activity was assessed using the 30-Day Physical Activity Recall, the 8-response physical activity self-report measure, and the International Physical Activity Questionnaire-short form. Level of need satisfaction for physical activity was assessed using the Perceived Need Satisfaction in Exercise Scale and student perception of need support was assessed using an expanded version of the Learning Climate Questionnaire. Physical activity enjoyment was assessed using a five-item version of the Exercise Enjoyment Scale and Stage of Change was assessed using a four-item questionnaire. For the substudy, a sample of students (N = 75) wore pedometers at the beginning and end of the semester for one week to objectively assess physical activity. In the substudy, a randomly selected sample of students (n = 34) wore a Fitbit Flex (Fitbit) everyday throughout the semester. The substudy comparison group (n = 41) did not wear a Fitbit monitor. The Fitbit is a commercially available monitor that can be used to assess physical activity, provide feedback, self-monitor, and set goals. Intervention effectiveness was evaluated with a series of mixed model analyses of variance and effect size estimates via Cohen's delta (d). RESULTS: Results indicated no meaningful differences in students' perception of need-support between the need-supportive and conventional teaching conditions (d = 0.13 to 0.19). For the main study, changes in self-determined motivation for physical activity, self-reported physical activity level, physical activity enjoyment, and Stage of Change across time points did not differ by teaching condition (p > .05, d < 0.15). In the substudy, students in the conventional teaching condition increased an average of 621 steps per day from time 1 to time 3, while students in the need-supportive teaching condition decreased by an average of 816 steps per day from time 1 to time 3. The difference in step changes from time 1 to time 3 across teaching conditions was medium to large (d = 0.66). In the substudy, all students showed decreases in objectively measured steps per day from time 1 to time 3, possibly due to the time of the semester in which the pedometer assessment was conducted. However, students who wore a Fitbit had a lesser decrease in steps per day (decrease of 104 steps per day, d = -0.05) compared to students who did not wear a Fitbit (decrease of 461 steps per day, d = -0.18). The effect size of the difference in changes in steps per day between Fitbit groups was small (d = 0.16). From time 1 to time 3, self-reported physical activity increased more in the students who wore a Fitbit than in students who did not wear a Fitbit (d = 0.28 to 0.32). Changes in self-determined motivation for physical activity, physical activity enjoyment, and Stage of Change were similar for Fitbit groups (p > .05, d < 0.16). Intrinsic regulation was the only motivational variable that increased more among students who wore a Fitbit compared to students who did not wear a Fitbit (d = 0.33). CONCLUSIONS: The need-supportive teaching condition had no meaningful effect on changes in any variable across time. A true disparity between the need-supportive and conventional teaching conditions was not created in the current study, which may explain why no teaching condition effect was found. Results of the substudy suggest that commercially available activity monitors, such as the Fitbit, can have a small positive impact on physical activity and intrinsic regulation for physical activity. Further intervention research should be conducted in university and college physical activity class settings to determine aspects of teaching environments that help students make choices that result in physically active lifestyles.
Keywords: Kinesiology; Physical education; Behavioral sciences; Colleges; Fitbit; Interventions; Need support; Physical activity class; Self-determination theory; Physical education for college students; Exercise; College students--Health and hygiene; Motivation (Psychology)